2005
DOI: 10.1186/bcr1036
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer properties of propofol-docosahexaenoate and propofol-eicosapentaenoate on breast cancer cells

Abstract: Introduction Epidemiological evidence strongly links fish oil, which is rich in docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), with low incidences of several types of cancer. The inhibitory effects of omega-3 polyunsaturated fatty acids on cancer development and progression are supported by studies with cultured cells and animal models. Propofol (2,6-diisopropylphenol) is the most extensively used general anesthetic-sedative agent employed today and is nontoxic to humans at high levels (50 µg/ml).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(72 citation statements)
references
References 45 publications
2
69
0
1
Order By: Relevance
“…However, these data seemed to contradict those obtained by means of the caspase-3 assay, which displayed activation after 24 h. This implies that a more significant number of condensed nuclei would have been visible at 24 and 48 h. It is probable that the cells, having reacted to DHA by activating caspase-3, had completely disappeared by 48 h, and this might explain the low incidence of condensed nuclei; several hours were generally needed to ensure that a cell went through the phenomenon of complete apoptosis once it had undergone the action of caspase-3. Indeed, the increasing numbers of condensed nuclei, which under our conditions reached their highest level of 11% after a longer incubation time, was consistent with the study reported by Siddiqui et al (20), in which the percentage of cells undergoing apoptosis leveled off at 15%. It is also possible that DHA can induce several different pathways leading to apoptosis, and in particular, the Bax pathway that has been described for the HL60 cell line (13).…”
Section: Discussionsupporting
confidence: 81%
“…However, these data seemed to contradict those obtained by means of the caspase-3 assay, which displayed activation after 24 h. This implies that a more significant number of condensed nuclei would have been visible at 24 and 48 h. It is probable that the cells, having reacted to DHA by activating caspase-3, had completely disappeared by 48 h, and this might explain the low incidence of condensed nuclei; several hours were generally needed to ensure that a cell went through the phenomenon of complete apoptosis once it had undergone the action of caspase-3. Indeed, the increasing numbers of condensed nuclei, which under our conditions reached their highest level of 11% after a longer incubation time, was consistent with the study reported by Siddiqui et al (20), in which the percentage of cells undergoing apoptosis leveled off at 15%. It is also possible that DHA can induce several different pathways leading to apoptosis, and in particular, the Bax pathway that has been described for the HL60 cell line (13).…”
Section: Discussionsupporting
confidence: 81%
“…12,34,39 These approaches were designed either to increase efficacy or enhance the specificity of targeted cells. Wang et al combined the use of DHA with the anticancer drug etoposide (VP16) to induce apoptosis in medulloblastoma cell lines, Daoy and D283, and glioblastoma cell lines, U87 and U138.…”
mentioning
confidence: 99%
“…Mammoto et al showed that clinically relevant concentrations of propofol (1-5 μg/ml) decreased the invasion ability of human cancer cells (HeLa, HT1080, HOS and RPMI-7951) in vitro, and furthermore, propofol induced lung metastasis of tumor cells in a mouse model of osteosarcoma (12). Siddiqui RA et al showed that the propofol-DHA or propofol-EPA conjugates significantly inhibit adhesion, migration and induced apoptosis of breast cancer cells, implying that these conjugates may be useful for the treatment of breast cancer (6). However, there are some different results, demonstrating that propofol could enhance the migration of human breast cancer cell lines (13).…”
Section: Discussionmentioning
confidence: 99%